STUDIES OF LITHOGENEUS SEDIMENT TRANSPORT IN THE ESTUARY OF MESJID RIVER DUMAI REGENCY RIAU PROVINCE - Yogie Novri Yusda; Rifardi '; Musrifin Ghalib (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted on November 2015 in the Estuary of Mesjid River of Dumai Regency, Riau Province. The aims to determine the amount of lithogeneus sediment that was transported through. Estuary of Mesjid. Determination of sampling points by purposive sampling, Method of sampling, where the sampling point taken was considered to represent the state of the overall area of research. Based on this sampling locations were divided into 8 sampling points. Sampling was carried out by using a water bottle sampler vandorn into three depths, i,e surface, middle and bottom waters. Measurement of current performed at the sampling point 2. Accumulated of sediment to calculate the accumulation of by using sediment traps placed at the sampling point retrieval is done 2 times a day that is at low tide and low tide 1 and 2 that at the. The amount of lithogeneus sediment transport is computed the average amount of sediment transport that comes out for seven days. Then converted data of sediment transport for 1 year, The results showed that the waters of the estuary at low tide greatly influenced by mass of river water by the discharge of 29,76 m3 / sec which is capable of transporting lithogeneus sediment amounted to 78,176 ton / year, of the rate of accumulation of sediment per year for every hectare of the sediment will settle at 289,16 ton / ha / year in waters around the estuary.Keyword : Sediment Transport, Sediment Lithogenous, Estuary of Mesjid